2009
DOI: 10.1016/j.biopsych.2009.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Lateralized Response Timing Deficits in Autism

Abstract: Background Procedural learning is an implicit process in which a behavioral response is refined through repeated performance. Neural systems supporting this cognitive process include specific frontostriatal systems responsible for the preparation and timing of planned motor responses. Evaluating performance on procedural learning tasks can provide unique information about neurodevelopmental disorders in which frontostriatal disturbances have been reported, such as autism. Methods Fifty-two individuals with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 46 publications
9
21
0
Order By: Relevance
“…Our computational results agree with reported ASD saccade abnormalities in human subjects (12-15), although reports are inconsistent (32,33). However, an ASD study showing no saccade abnormalities did find differences in functional imaging that might indicate compensatory mechanisms that helped to equalize saccade performance (33).…”
Section: Discussionsupporting
confidence: 91%
“…Our computational results agree with reported ASD saccade abnormalities in human subjects (12-15), although reports are inconsistent (32,33). However, an ASD study showing no saccade abnormalities did find differences in functional imaging that might indicate compensatory mechanisms that helped to equalize saccade performance (33).…”
Section: Discussionsupporting
confidence: 91%
“…Similar findings were reported in a study of visually guided saccades, with increased activation of pre-SMA, DLPFC, and dorsomedial thalamus in HFA individuals [11*]. However, these results were attributed to an atypical way of utilizing frontal cortex to initiate simple motor acts resulting from atypical brain development, as procedural learning, an implicit process, was found to be intact in HFA [12]. …”
Section: Broad Involvement Of Cortical Systems and Higher Order Abilisupporting
confidence: 83%
“…We propose that the method developed here could be useful for examining coordination in impaired populations. Coordinative or state-dependent timing is thought to depend on the cerebellum (Diedrichsen et al 2007) and basal ganglia (Wu et al 2010), and deficits have been observed in subjects with a wide range of neurological disorders, including adults with Parkinson's disease (Gross et al 2008;Tagliabue et al 2009), Huntington's disease (Klein et al 2010), and cerebellar lesions (McNaughton et al 2004) and children with reading delay autism (D'Cruz et al 2009) and attention-deficit/hyperactivity disorder (Frings et al 2010). Intrinsic timing deficits have even been proposed to be central to the etiology of schizophrenia (Andreasen et al 1998;Andreasen and Pierson 2008).…”
Section: Discussionmentioning
confidence: 99%